ANALISIS KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VII SMP NEGERI KOTA JAMBI - Ayu Yarmayani; Risma Simamora (Pendidikan Matematika | STKIP YM Bangko, 2021)
This study aims to determine the level of ability to comprehend the concept of mathematical high students have the ability to understand good concept and able to solve every problem correctly that meet the indicators of concept understanding this is (a) Ability to re-state a concept; (b) the ability to develop necessary terms or sufficient conditions from a concept; (c) Ability to use, utilize and select certain procedures; and (d) Ability to apply concepts to problem solving. Meanwhile, the level of ability to understand the concept of low students don’t have the ability to understand good mathematical concepts and students have not been able to use the concepts that have been studied to solve the problem. The ability to comprehend low mathematical concepts of students is only able to meet 2 of the 4 indicators understanding the concept provided but not the maximum. Indicators that are fulfilled are (a) re-state a concept only partially; and (2) Ability to use, utilize and select certain procedures.